Maintaining Balance when Looking at a Virtual Reality Three-Dimensional Display of a Field of Moving Dots or at a Virtual Reality Scene - Chiarovano, Elodie; de Waele, Catherine; MacDougall, Hamish G.; Rogers, Stephen J.; Burgess, Ann M.; Curthoys, Ian S. (Frontiers in Neurology, 2015)
Experimental objective. To provide a safe, simple, relatively inexpensive, fast, accurate way of quantifying balance performance either in isolation, or in the face of challenges provided by 3D high definition moving visual stimuli as well as by the proprioceptive challenge from standing on a foam pad. This method uses the new technology of the Wii balance board to measure postural stability during powerful, realistic visual challenges from immersive virtual reality. Limitations of current techniques. Present computerized methods for measuring postural stability are large, complex, slow and expensive, and do not allow for testing the response to realistic visual challenges. Protocol. Subjects stand on a 6cm thick, firm, foam pad on a Wii balance board. They wear a fast, high resolution, low persistence, virtual reality head set (Oculus Rift DK2). This allows displays of varying speed, direction, depth and complexity to be delivered. The subject experiences a visual illusion of real objects fixed relative to the world, and any of these displays can be perturbed in an unpredictable fashion. A special app (Balance Rite) used the same procedures for analysing postural analysis as used by the Equitest. Power of the technique. Four simple “proof of concept” experiments demonstrate that this technique matches the gold standard Equitest in terms of the measurement of postural stability but goes beyond the Equitest by measuring stability in the face of visual challenges, which are so powerful that even healthy subjects fall. The response to these challenges presents an opportunity for predicting falls and for rehabilitation of seniors and patients with poor postural stability. Significance for the field. This new method provides a simpler, quicker, cheaper method of measurement than the Equitest. It may provide a new mode of training to prevent falls, by maintaining postural stability in the face of visual and proprioceptive challenges similar to those encountered in life.